2012
DOI: 10.1128/aem.01675-12
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Thiamine Pyrophosphate-Dependent 2-Oxo-Acid Decarboxylases in Saccharomyces cerevisiae

Abstract: dFusel alcohols are precursors and contributors to flavor and aroma compounds in fermented beverages, and some are under investigation as biofuels. The decarboxylation of 2-oxo acids is a key step in the Ehrlich pathway for fusel alcohol production. In Saccharomyces cerevisiae, five genes share sequence similarity with genes encoding thiamine pyrophosphate-dependent 2-oxoacid decarboxylases (2ODCs). PDC1, PDC5, and PDC6 encode differentially regulated pyruvate decarboxylase isoenzymes; ARO10 encodes a 2-oxo-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 64 publications
4
81
0
Order By: Relevance
“…For example, while ARO9 and ARO10 transcripts increased in the cold at exp, they had reduced at stat to be unchanged from 25°C. In contrast, the CHA1 transcript [implicated in threonine degradation at the same step as Aro9p (Romagnoli et al 2012)] was lower in the cold at exp, and remained depressed even at stat.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…For example, while ARO9 and ARO10 transcripts increased in the cold at exp, they had reduced at stat to be unchanged from 25°C. In contrast, the CHA1 transcript [implicated in threonine degradation at the same step as Aro9p (Romagnoli et al 2012)] was lower in the cold at exp, and remained depressed even at stat.…”
Section: Resultsmentioning
confidence: 60%
“…Furthermore, the NCR-regulated glutamate/aspartate permease, DIP5, was 3.3-fold down-regulated in the cold at exp. Conversely, the ARO9 [catabolism of phenylalanine and methionine; (Romagnoli et al 2012)] and ARO10 transcripts [catalysing the subsequent step in the catabolism of multiple amino acids; (Romagnoli et al 2012)] were both induced, consistent with elevated amino acid catabolism at low temperature during exponential growth. The differential expression of amino acid biosynthesis and degradation genes occurred in both directions, and was not always consistent at the two different time points, suggesting that there was not a simple shift in amino acid metabolism with temperature.…”
Section: Resultsmentioning
confidence: 90%
“…Decarboxylation of phenylpyruvate, the 2-oxo acid associated to phenylalanine, yields phenylacetaldehyde, which is subsequently reduced into phenylethanol and/or oxidized to phenylacetate [41-43]. Decarboxylation of phenylpyruvate can be catalyzed by four different thiamine pyrophosphate-dependent 2-oxo acid decarboxylases encoded by ARO10, PDC1, PDC5, and PDC6 [43,44]. Recent work in our group has demonstrated that, among the four decarboxylases capable of phenylpyruvate decarboxylase, Pdc1 and Pdc6 showed a much lower affinity and decarboxylation rate of phenylpyruvate than Pdc5 and, in particular, Aro10 [44].…”
Section: Resultsmentioning
confidence: 99%
“…Decarboxylation of phenylpyruvate can be catalyzed by four different thiamine pyrophosphate-dependent 2-oxo acid decarboxylases encoded by ARO10, PDC1, PDC5, and PDC6 [43,44]. Recent work in our group has demonstrated that, among the four decarboxylases capable of phenylpyruvate decarboxylase, Pdc1 and Pdc6 showed a much lower affinity and decarboxylation rate of phenylpyruvate than Pdc5 and, in particular, Aro10 [44]. Since absence of all three pyruvate decarboxylase genes ( PDC1 , PDC 5 and PDC6 ) abolishes growth on glucose in synthetic media, strains only retaining PDC1 ( aro10Δ, pcd5Δ, pdc6Δ ) were constructed [45].…”
Section: Resultsmentioning
confidence: 99%
“…The flavor of fermented foods and beverages is characterized by many low-molecular-weight flavor compounds (e.g., short-chain alcohols, aldehydes, organic acids, and esters) (28,29). These compounds are produced by several microorganisms that are involved in fermentation, and they have a strong impact on product quality.…”
Section: Discussionmentioning
confidence: 99%